How Helminths Alter Immunity to Infection - Horsnell, William (Advances in Experimental Medicine and Biology, 2014)
Helminth infections are common, cause considerable pathology, and alter a host's immune profile. This can have important consequences not only on the host's ability to control a helminth infection, but also on their ability to control unrelated infections. In endemic areas, understanding how helminth infection influences the outcome of common infectious diseases and changes the efficacy of childhood vaccination programs is an important public health question. This book reviews how host immunity to helminths alters our ability to respond to the major pathogens that exist in helminth endemic regions. Current understanding of how helminths alter important but relatively neglected contributors to the host's anti-helminth immune responses are addressed, namely host antibody responses and how maternal infection may alter a child's immune development. These are discussed in relation to the control of helminth infection and unrelated infections. Also covered are how helminth infections alter the host's ability to control TB, HIV and malarial infections along with neglected bacterial infections, such as cholera, and how endemic helminth infections are likely to alter our ability to respond to life-saving vaccination strategies.